(untitled) (Jalalabad Medical Journal, 2025)
Iron deficiency (ID) is the most common nutritional deficiency in the world. Infants and young children are at the highest risk. Impaired growth, mental retardation, increased susceptibility to infection, poor school performance, and poor activity are the long-term consequences of iron deficiency anaemia. The aim of this study was to determine the prevalence of iron deficiency anaemia among children aged 6-59 months. This cross-sectional study was carried out in the department of Paediatrics, Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet from March 2021 to August 2021. A total of one hundred nineteen (119) admitted children in the Paediatrics ward were enrolled by consecutive sampling. The majority of the children (55.5%) were between the ages of 6 and 12 months. Iron-deficiency anaemia (IDA) was identified in 48.7% of children, and more than half of the male children (55.4%) were suffering from IDA. Serum ferritin and transferrin saturation, which are the primary indicators of IDA, were significantly decreased and red cell distribution width was significantly increased in children with IDA (p<0.05). The current study found that 6-59-months-old, hospitalized children in Sylhet had a higher prevalence of IDA. Public health intervention should be established to counter the problem. Jalalabad Med J 2022; 19 (1): 27-30